Time-windows constrained electric logistics vehicle routing optimization model and its dispatching benefits analysis in the energy market - Jiwei Wang; Jun Mo; Hui Yang (International Journal of Electrical Power & Energy Systems)
The scheduling benefits of electric logistics vehicles through charging and discharging time regulation have not been fully recognized or explored in previous studies. This paper introduces the concept of charging and discharging time windows and proposes an electric logistics vehicle charging and discharging scheme based on demand response. For the price-based demand response mechanism, the electric logistics vehicle routing with time windows optimization model is constructed, with the travel routes and distance matrix calculated using the adaptive chaotic genetic algorithm and dueling Deep Q-Network, respectively. For the relationship between the power grid operator and the logistics operator, a master–slave game model based on the incentive-based demand response mechanism is constructed and simplified using the kriging metamodel. Our results demonstrate significant scheduling benefits: the logistics operator’s operating costs are reduced by 5.59% and 8.22% under the price-based and incentive-based demand response mechanisms, respectively, while the power grid operator reduces operational losses by 29.96% through game interactions with the logistics operator.